Anatomical Tool as Additional Approach for Identifying Pharmaceutically Important Ephedra Species (Ephedraceae) at Gender Identity Level in Egypt - Maha H. Khalaf; Wafaa M. Amer; Najla A. Al Shaye; Mahmoud O. Hassan; Nasr H. Gomaa (Biology)
The genus Ephedra Tourn. ex L. (Ephedraceae) is an important source with pharmacological and environmental potential. Conversely, Ephedra spp. still exhibit taxonomic complexity, especially for the specimens lacking reproductive cones. This complexity is attributed to its xeromorphic features, notably the reduced leaves and analogous assimilating branches, which make the species identification a real challenge. The current study provides a pioneering approach to distinguish fragments of Ephedra species at the gender level. This study was based on the stem anatomy and stem epidermal features using a light microscope for five species (E. alata Decne., E. aphylla Forssk., E. ciliata Fisch. & C.A.Mey., E. foeminea Forssk. and E. Ephedra pachyclada Boiss.) represented by ten genders collected from S. Sinai, Egypt. Anomocytic and brachyparacytic stomata, tanniniferous idioblasts, annual rings, a terete and furrowed outline, the number and width of tracheids, patches of cortical fibers, unicellular trichomes, druses, solitary crystals, and the activity of interfascicular cambium were among the distinguishing features that were found. Different statistical analyses were applied to explore the diversity at interspecific and intra-generic levels. This study revealed that the stem anatomy was not only an efficient tool for identifying the investigated five Ephedra species at the species level but also presented a differential key to distinguish between genders and species. In addition, our results indicated that the epidermal features played a critical role in differentiating the studied Ephedra species at the gender level. This study confirms the efficacy of stem anatomy as an identification approach for the Ephedra species at the gender level and recommends this approach to identify the fragmented Ephedra for taxonomical, pharmaceutical, and medical applications.